Investigation of Essential Oil from Cumin (Cuminum cyminum) Seeds and Selected Terpenes as Repellents Against Adult Female Phlebotomus papatasi (Scopoli) (Diptera: Psychodidae) Sand Flies - Maia Tsikolia; Panagiota Tsafrakidou; Michael Miaoulis; Andrew Y. Li; Dawn Gundersen-Rindal; Alexandra Chaskopoulou (Insects, 2025)
Leishmaniasis, a parasitic disease transmitted by sand flies, poses a significant global health threat. Chemical repellents and insecticides are widely used for protection, but prolonged use has led to resistance, reduced efficacy, and environmental concerns, emphasizing the need for new repellent compounds, ideally from sustainable sources. This study investigated the chemical composition and repellent properties of cumin seed essential oil (EO) from Greece against Phlebotomus papatasi. Gas chromatography–mass spectrometry (GC-MS) identified five major constituents, including cumin aldehyde (27.0%), β-pinene (11.4%), and γ-terpinene (10.8%). In addition to cumin seed EO and its major constituents, octanol, and 1-octen-3-ol were tested for comparison, along with transfluthrin and DEET as standard repellents. Using a static air repellency bioassay, cumin seed EO, cumin aldehyde, and octanol exhibited strong spatial repellency (EC50 of 0.34, 0.07, and 0.60 μg/cm2 respectively) comparable to transfluthrin (EC50 of 0.04 μg/cm2) at 1 h, and contact repellency, both lasting up to 3 h. This is the first study to evaluate cumin seed EO and cumin aldehyde against sand flies, highlighting their potential as alternatives to conventional repellents. Further research is needed to explore their applicability in vector control strategies.